Une théorie économique du loisir industriel : le cas du Canada - Poulin Simon, Lise (L'Actualité économique)

(untitled) (HEC Montréal, 1981)
ABSTRACTContemporary economic theory explains the historical evolution in industrial leisure, the change in the time spent working on the labor market with the aid of a single variable, price. This article proposes a different explanation of the determination of industrial leisure. The fundamental economic conditions that have affected industrial leisure, it is argued, are unemployment, industrial development which has modified the composition of jobs and the complementary between entrepreneurial and white-color occupations. This thesis which has emerged following a study of the historical evolution of industrial leisure in Canada since Confederation focuses on the three dimensions of leisure: the length of the normal work week, labour force non-participation and paid vacations and holidays.